Clinicopathological correlation of Bcl-2 oncoprotein expression in oral precancer and cancer - Vandana Arya; Subash Singh; M. Jonathan Daniel (Elsevier, 2016)
Oral squamous cell carcinoma is the most common malignant tumor of the oral cavity. Normally the death of cell and the growth are active processes and depend not only on external factors but also on the expression of genes such as Bcl-2, which activate and inhibit apoptosis. The term Bcl-2 is an acronym for B-cell lymphoma/leukemia-2 genes. It has been reported that there is deregulation of Bcl-2 expression during progression from oral epithelial dysplasia to squamous cell carcinoma.Expression of this oncoprotein can be detected by immunohistochemistry. Aims and objectives: An attempt was made to evaluate Bcl-2 oncoprotein expression in patients with oral precancer and cancer. Materials and methods: A selective prospective clinical and immunohistochemical study. Clinicopathological examination was correlated with immunohistochemical findings. The immunolocalization of Bcl-2 protein was performed using the labeled streptavidin biotin method. To visualize the reaction, 3,3-diaminobenzidine was used. Results: Bcl-2 expression was positive in 11 [36.66%, low Bcl-2 expression 3 (10.00%), moderate Bcl-2 expression 7 (23.33%), and high Bcl-2 expression 1 (3.33%)] oral cancer cases and 14 [87.50%, low expression 8 (50%), moderate expression 6 (37.50%)] precancer cases. Conclusion: On the basis of the results of our study, we conclude that positive Bcl-2 expression may be an indicator of poor prognosis in oral cancer and precancer.